Development of Sales Lead Management in CRM Context - Huhta-Kahma, Kati (My University, 2014)
This thesis is done as an assignment for Wärtsilä Corporation’s Services unit. The purpose is to study sales lead management in Customer Relationship Management context in order to find out how sales lead management can be developed in the case company. Typical problems in sales lead management are inconsistent quality of leads, lack of lead qualification and analyses regarding the success of lead generation. CRM system is in a key role for providing customer data and for managing sales leads. Companies can work proactively on generating leads that support their business. Marketing should provide enough qualified leads for sales to work on, but the quality of the leads shall always be more important than the quantity. The theory of the thesis is based on literature concerning relationship marketing, customer relationship management and sales lead management. A desk study based on data in the CRM system gave an overview on the success of the leads in the case company. The empiric part of the thesis and the primary source for information is a qualitative research which was conducted by half-structured thematic interviews. Key persons in Wärtsilä Services sales and marketing organisations were interviewed. Sales lead management should be seen as a multi-step process, where leads are identified and generated proactively. When the most valuable lead sources are known, marketing money and time can be used for them. The main development areas were identified in the sales lead management based on the findings of the study. Improvement suggestions were made for all stages in the sales lead management end-to-end process in the case company.
Keywords: Customer Relationship Management; CRM; customer relationship management system; sales lead management; fi=Markkinointi|en=Marketing|; fi=Markkinoinnin johtamisen maisteriohjelma|en=Master's Programme in Marketing Management|